Adsorption of 2, 4-dichlorophenol on paper sludge/wheat husk biochar: Process optimization and comparison with biochars prepared from wood chips, sewage sludge and hog fuel/demolition waste. Issue 3 (June 2017) - Kalderis, Dimitrios; Kayan, Berkant; Akay, Sema; Kulaksız, Esra; Gözmen, Belgin
Abstract: The adsorption of 2, 4-dichlorophenol, a toxic by-product of triclosan commonly found in wastewater treatment plant effluents, was studied on paper sludge/wheat husks biochar. By using response surface methodology, the optimum conditions and effects of pH, temperature, initial 2, 4-DCP concentration and time were determined. The solution pH was found to be the most influential parameter whereas the optimum adsorption conditions were predicted as: C0  = 40.28 mg L −1, T = 326 K, pH = 2.8, t = 143 min, where a 99.95% adsorption could be achieved. Both Langmuir and Freundlich provided a good fit for the experimental data, indicating a surface and multi-layer adsorption. Kinetically, the process primarily followed the pseudo-second order model (chemisorption). By comparing the adsorption capacity at equilibrium of our main biochar (qe  = 9.28 mg g −1 ) to 3 biochars prepared from different biomasses (qe values 1.57–2.96 mg g −1 ), it was concluded that pH-dependent electrostatic interactions and non-covalent π-electron donor-acceptor mechanisms play the most important role. Finally, there was indication that high concentrations of Ca and K may promote the adsorbate-adsorbent interactions and enhance adsorption.